Translation and psychometric evaluation of the Turkish version of the pharmacy students' perceptions of preparedness to provide pharmaceutical care scale - OKUYAN, BETÜL; AY, NADİYE PINAR; RABUŞ, ŞULE (GOVI-VERLAG PHARMAZEUTISCHER VERLAG GMBH, 2016)
The aim of the study is to conduct the psychometric evaluation of the Turkish version of the Pharmacy Students' Perceptions of Preparedness to Provide Pharmaceutical Care (PREP) scale. The present study was conducted at three faculties of pharmacy among fifth-year students during a three-month period in 2015. After the translation process, the Turkish version was developed. Psychometric evaluation consisted of the calculation of inter-rater and test-retest reliability and factor analysis. The mean age of 184 students (71.2% of female) was 23.74 +/- 1.07. The mean score of the Pharmacy Students' PREP scale was 4.54 +/- 1.00 and the Cronbach's alpha was 0.971. Inter-rater and test-retest reliability and factor analysis were also in concordance with the literature. In the present study, the Turkish version of Pharmacy Students' Perceptions of Preparedness to Provide Pharmaceutical Care Scale has been determined to be a reliable and validated tool to assess students' perceptions of preparedness to provide pharmaceutical care.